Genomic instability in individuals with sex determination defects and germ cell cancer - Krivega, Maria; Zimmer, Jutta; Slezko, Anna; Frank-Herrmann, Petra; Rehnitz, Julia; Hohenfellner, Markus; Bettendorf, Markus; Luzarowski, Marcin; Strowitzki, Thomas (Cell death discovery, 2023)
The ability to transmit genetic information through generations depends on the preservation of genome integrity. Genetic abnormalities affect cell differentiation, causing tissue specification defects and cancer. We addressed genomic instability in individuals with Differences of Sex Development (DSD), characterized by gonadal dysgenesis, infertility, high susceptibility for different types of cancer, especially Germ Cell Tumors (GCT), and in men with testicular GCTs. Whole proteome analysis of leukocytes, supported by specific gene expression assessment, and dysgenic gonads characterization, uncovered DNA damage phenotypes with altered innate immune response and autophagy. Further examination of DNA damage response revealed a reliance on deltaTP53, which was compromised by mutations in the transactivation domain in DSD-individuals with GCT. Accordingly, drug-induced rescue of DNA damage was achieved by autophagy inhibition but not by stabilization of TP53 in DSD-individuals’ blood in vitro. This study elucidates possibilities for prophylactic treatments of DSD-individuals, as well as new diagnostic approaches of GCT.
Gesehen am 16.06.2023